PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN YANG BERDAMPAK PADA MINAT MENGGUNAKAN ULANG APLIKASI GO-JEK DI KOTA PONTIANAK - PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN PERSEPSI HARGA TERHAD, Meychell (Jurnal Manajemen Update, 2018)
The development of information and communication technology is bringing an impact on the business. The business that previously offline now becoming online. Online business or electronic commerce (E-commerce) is an electronic exchange process that occurs between several parties, either individually, organization, or both. This study aims to analyze the influence of perceived usefulness, perceived ease of use, and perceived price on customer satisfaction and its impact on re-use intention. This research is an associative research. Data was obtained by online questionnaires to users of Go-Jek applications in Pontianak City with the number of respondents as many as 100 people. This study using convenience sampling with analytical tool used is path analysis.The result of the first substructure show that perceived usefulness, perceived ease of use, and perceived price have an positive impact on customer satisfaction. While the result of the second substructure indicate perceived usefulness and customer satisfaction have an positive impact on re-use intention, meanwhile perceived price has no impact to re-use intention on Go-Jek application.Keywords: Perceived Usefulness, Perceived Ease of Use, Perceived Price, Customer Satisfaction, Re-use Intention, TAM